2013
DOI: 10.1111/jfb.12152
|View full text |Cite
|
Sign up to set email alerts
|

Can backcalculation models unravel complex larval growth histories in a tropical freshwater fish?

Abstract: This experimental study compared the precision and accuracy of the biological intercept (BI), modified fry (MF) and time-varying growth (TVG) backcalculation models in estimating the early growth of the tropical freshwater purple-spotted gudgeon Mogurnda adspersa. Larvae were reared up to 41 days post hatching under two temperatures and four different feeding regimes. Food and temperature treatments induced complex growth profiles among fish, and although total length (LT ) and otolith radius were related unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Growth of fishes is linked to appropriate conditions of the inhabited environment in food availability and water temperature (Starrs et al., ) and salinity (Bœuf and Payan, ). In our experimental design the salinity level was the only difference among treatments, while food availability and temperature were held constant.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of fishes is linked to appropriate conditions of the inhabited environment in food availability and water temperature (Starrs et al., ) and salinity (Bœuf and Payan, ). In our experimental design the salinity level was the only difference among treatments, while food availability and temperature were held constant.…”
Section: Discussionmentioning
confidence: 99%
“…Larval growth rates were highly variable among individuals, with the largest larva being double the size of the smallest after 31 days. The average TL (11.68 mm) was less than that recorded in a previous study in which larvae were reared individually under variable food and temperature regimes (Starrs et al 2013). However, the range of growth rates observed in the two studies was comparable.…”
Section: Efficacy and Impacts Of Transgenerational Marking On Larvae mentioning
confidence: 39%
“…The larvae rearing system has been described previously (Starrs et al 2013) but was modified for the present study. Forty-eight clear plastic 5 L tubs were arranged in a row-column design on two racks (24 tubs per rack) in a light-and temperature-controlled room (13 h light : 11 h dark and 27.1 ± 0.5°C SE).…”
Section: Larval Morphology Survival and Growthmentioning
confidence: 99%
“…In the present study, the hot (218C) water temperature treatment during summer surpassed the optimum temperature for growth even for the juvenile Chinook fed the high (exceeded satiation) ration, representing a plausible explanation for the uncoupling in the otolith size-to-FL relationship between the cool and hot temperature treatments. Food deprivation has been shown to influence the otolith-to-somatic size relationship in other fish as a result of continued otolith development during periods when somatic growth is halted (Baumann et al 2005;Starrs et al 2013). Although the effect of prolonged starvation on increment formation has not been examined in post-smolt juvenile Chinook salmon, Neilson and Geen (1985) showed that alevins and fry produced at least one otolith increment per day across multiple rations, indicating some level of endogenously driven daily incremental deposition of CaCO 3 .…”
Section: Discussionmentioning
confidence: 99%